Impregnation of in-house synthesized carbon nanotubes in bacterial cellulose - Adnan, Sharmeen (2011)
Bacterial cellulose (BC) synthesized by Acetobacter xylinum has been discovered as a potential matrix for impregnating carbon nanotubes (CNT). The main objective of this study is to produce bacterial cellulose/carbon nanotube (BC/CNT) with improved hydrophobic surface. CNT addition is by mean to improve the electrical property of BC to be a conductive membrane. Hydrophobic membrane is more practical in device development since it can adhere with other hydrophobic material, which is achieved in this study by acetylation process. In this work, the membranes were produced using date extract (DE) culture medium. Three CNT impregnation techniques were tested, i.e. immersion, dispersion and spraying, whilst the acetylation conducted were homogeneous and heterogeneous processes. In this study, morphological characteristic is an important property for sample selection to be characterized further. BC/CNT nanocomposite produced via spraying technique has uniform CNT dispersion and has the most dielectric conductivity value i.e. ~4.66 x 10-1 S/cm than the other techniques. Therefore, spraying was used to prepare BC/CNT acetate nanocomposite. Since the morphology of BC/CNT acetate obtained from heterogeneous process proves that the acetylation only occurred on the surface and the inner core structures of the BC are still intact, this process was used further. The most significant characteristic of BC/CNT acetate is the existence of C=O, CH3 and C-O functional groups of acetyl and higher water contact angle (~77°) than that of BC/CNT (~45°). When tested, decomposition and glass transition temperatures of BC/CNT acetate have reduced by 203°C and 35°C respectively, compared to that BC/CNT. The reduction is occurred mainly because the swollen BC structure of BC/CNT acetate is easily degraded by heat treatment. The acetylated BC/CNT on the other hand, has higher crystal BC fraction, i.e. 51% compared to that of BC/CNT (49%). These findings indicate that the CNT hinders the degradation of nanocomposite and protects the BC crystals. Thus when acetylated, both elasticity and crystallite size of BC/CNT has only reduced by 9%, i.e., from 34 to 31 GPa and from 27.3 to 24.9 nm, respectively. The bigger pore size of the acetate nanocomposite (~22 Å) than that of BC/CNT (~-103 Å) might allows further functionalization process introduced to the membrane. As a conclusion, the CNT impregnation by spraying technique during the growing fermentation of BC coupled with heterogeneous acetylation treatment resulted in a more water resistant,increased dielectric conductivity and increased crystal BC fraction. While, the sheet elasticity,crystallite size, surface area, decomposition and glass transition temperatures became lower.These characteristics makes acetylated BC/CNT sheet a potential as a biomaterial membrane in device development.